Focal vs extended ablation in localized prostate cancer with irreversible electroporation; a multi-center randomized controlled trial. Issue 1 (December 2016) - Scheltema, Matthijs; van den Bos, Willemien; de Bruin, Daniel; Wijkstra, Hessel; Laguna, M.; de Reijke, Theo; de la Rosette, Jean
Abstract Background Current surgical and ablative treatment options for prostate cancer (PCa) may result in a high incidence of (temporary) incontinence, erectile dysfunction and/or bowel damage. These side effects are due to procedure related effects on adjacent structures including blood vessels, bowel, urethra and/or neurovascular bundle. Ablation with irreversible electroporation (IRE) has shown to be effective and safe in destroying PCa cells and also has the potential advantage of sparing surrounding tissue and vital structures, resulting in less impaired functional outcomes and maintaining men's quality of life. Methods/Design In this randomized controlled trial (RCT) on IRE in localized PCa, 200 patients with organ-confined, unilateral (T1c-T2b) low- to intermediate-risk PCa (Gleason sum score 6 and 7) on transperineal template-mapping biopsies (TTMB) will be included. Patients will be randomized into focal or extended ablation of cancer foci with IRE. Oncological efficacy will be determined by multiparametric Magnetic Resonance Imaging, Contrast-Enhanced Ultrasound imaging if available, TTMP and Prostate Specific Antigen (PSA) follow-up. Patients will be evaluated up to 5 years on functional outcomes and quality of life with the use of standardized questionnaires. Discussion There is critical need of larger, standardized RCTs evaluating long-term oncological and functional outcomes before introducing IRE and other focal therapy modalities as an accepted and safe therapeutic option for PCa. This RCT will provide important short- and long-term data and elucidates the differences between focal or extended ablation of localized, unilateral low- to intermediate-risk PCa with IRE. Trial registration Clinicaltrials.gov database registration numberNCT01835977 . The Dutch Central Committee on Research Involving Human Subjects registration number NL50791.018.14.